Biological Evaluation of Different Extracts of Aerial Parts of Nepeta deflersiana and Standardization of Active Extracts Using 8-Epi-7-Deoxyloganic Acid and Ursolic Acid by Validated HPTLC Method. (13th September 2018) - Orfali, Raha; Siddiqui, Nasir Ali; Alam, Perwez; Alhowiriny, Tawfeq Abdullah; Al-Taweel, Areej Mohammad; Al-Yahya, Sami; Majrashi, Najwa Mohammed; Mehmood, Rashad; Khan, Shabana Iqrar; Perveen, Shagufta
Abstract : Nepeta deflersiana (Lamiaceae) is a well-known medicinal plant that grows in Saudi Arabia. This plant is used in Saudi and Yemeni folk medicine as an anti-inflammatory, carminative, and antirheumatic agent. In order to prove its use in folk medicine, four different extracts from the aerial parts of the plant: petroleum ether, chloroform, ethyl acetate, and n -butanol extracts were subjected to biological assays to screen PPAR α and PPAR ϒ agnostic, antioxidant, anti-inflammatory, and cytotoxic activities. Ethyl acetate and n -butanol extracts of N. deflersiana NDEE and NDBE, respectively, showed a decrease in oxidative stress and inhibition of both NF-kB and iNOS activities with no cytotoxic effects on four human cancer cell lines. Both active extracts were standardized using two bioactive metabolites which were isolated from the aerial parts of the same plant [8-epi-7-deoxyloganic acid (compound 1 ) and Ursolic acid (compound 2 )] by developing a validated HPTLC method. It was found to provide a sharp and compact band of compound 1 at R f = 0.07 and R f = 0.57 for compound 2, using chloroform, methanol, and formic acid (8.9:0.8:0.3, v/v/v) as mobile phase at 550 nm. Compounds 1 and 2 were found in NDEE by 9.59 %, w/w, and 84.63 %, w/w, respectively, and by 11.97 %, w/w, and 21.26 %, w/w, respectively, in NDBE.